Tomada de decisão de Psicólogos em avaliação Psicologica - Lopes, Adriana Coura Feitosa (2014)
Psychological assessment is a procedure that is inserted in all areas of a psychologist s professional field of work. When starting any psychological intervention, it is necessary to carry an analysis of how individual operate in order to identify and define their demands to adequately meet them. It is important to study this practice because the choice of instruments, techniques and procedures to be employed influences the efficiency and effectiveness of the work and the image of the profession towards society in general, also impacting the scientific community. This study aimed to identify, in the subjects, the percentage of professionals in psychology who make use of the Psychological Assessment in the Northeastern region of Brazil; another objectives were to analyze the profile of these professionals in terms of gender, time after graduation, additional training in PA, the state of the country where he/she works; to check how psychologists do their planning when using PA as well as to identify which differences can be observed in terms of time from graduation and additional training in the process of planning the assessment different extents. The instrument used was an online questionnaire and the sample was by adhesion to the application. The attendance was of 159 professionals and most of them were females with a specialist degree. It was found that the majority of the professionals perform the planning of the PA, establishing a method and choosing the most appropriate strategies to be used. It was also verified that most of the subjects fulfill the steps of the whole process, and when planning the techniques of data collection, integrating database from different sources, reporting the results and returning the information, the professional demonstrates his/her goals to understand their demands and accomplish the decision making and/or proposed intervention for individuals assessed. It was found that the undergraduate degree may not have produced a more complete effect in the professional qualification and therefore, of the quality of the actions in PA, and that there is a need for training and continuing education